By blood or by choice? On relational autonomy and the familial ties that bind us - Van Wyk, Tanya (Stellenbosch Theological Journal, 2022)
This article explores the range of the construct "family" in light of the author's experience of how the death of a congregation-member exposed the strength, persistence and immovability of the construct, "family". Despite different attempts and approaches to deconstruct and broaden the notion of what family refers to that originated in the 1970s, a traditional notion of what kinship (family) entails remains focused on ties that bind people by blood or by marriage. The article provides a brief overview and evaluation of different attempts at a postmodern understanding of family, but ultimately it is illustrated that there has been little change to the construct of family. The notion of "relational autonomy" from a Trinitarian theological perspective is presented as a more thorough foundation for familial ties that are characterised by a creative tension of both distance and belonging. This theological foundation provides a point of departure for a dynamic understanding of the range of choices related to what constitutes, "family", which does not cast someone in the stone of the construct of a "family", even beyond their own death.